2019
DOI: 10.1371/journal.pone.0216718
|View full text |Cite
|
Sign up to set email alerts
|

State of the art forensic techniques reveal evidence of interpersonal violence ca. 30,000 years ago

Abstract: The Cioclovina (Romania) calvaria, dated to ca . 33 cal ka BP and thought to be associated with the Aurignacian lithic industry, is one of the few relatively well preserved representatives of the earliest modern Europeans. Two large fractures on this specimen have been described as taphonomic modifications. Here we used gross and virtual forensic criteria and experimental simulations on synthetic bone models, to investigate their nature. Both forensic trauma pattern analysis and experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 38 publications
0
16
0
1
Order By: Relevance
“…All the comparisons between the figures in Kranioti et al () with the original photographs and radiograph in Rainer and Simionescu () establish without a doubt (a) the completeness of the Cioclovina 1 calvaria at the time of discovery and during its post‐recovery description and (b) the breakage of the cranium subsequent to its original description. The damage took place during World War II, combined with a subsequent incomplete restoration of the skull.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…All the comparisons between the figures in Kranioti et al () with the original photographs and radiograph in Rainer and Simionescu () establish without a doubt (a) the completeness of the Cioclovina 1 calvaria at the time of discovery and during its post‐recovery description and (b) the breakage of the cranium subsequent to its original description. The damage took place during World War II, combined with a subsequent incomplete restoration of the skull.…”
Section: Resultsmentioning
confidence: 83%
“…Old versus new: (a) Kranioti et al () right superolateral view of Cioclovina 1 with details of the depressed area of the right parietal bone (reproduced from their Figure ; https://doi.org/10.1371/journal.pone.0216718.g001); (b) original superior view from Rainer; (c) original right lateral view from Rainer…”
Section: The Current Condition Of Cioclovinamentioning
confidence: 99%
See 1 more Smart Citation
“…Trauma patterns can serve as an important measure of the lifestyle, organization, and stresses of past human populations, since traumatic injuries are directly linked to violent encounters (Churchill, Franciscus, McKean-Peraza, Daniel, & Warren, 2009;Kranioti, Grigorescu, & Harvati, 2019;Larsen, 2015;Martin, Debra, & Anderson, 2014;Martin, Debra, & Harrod, 2015;Mirazón Lahr et al, 2016;Redfern, 2017b;Sala et al, 2015;Wahl & Trautmann, 2012;Walker, 2001), accidents (Kappelman et al, 2016;L'Abbé et al, 2015;Marinho & Cardoso, 2016;Petaros et al, 2013), impairments and care for the injured (Spikins et al, 2019;Spikins, Needham, Tilley, & Hitchens, 2018;Stodder, 2017;Tilley, 2015Tilley, , 2017Trinkaus, 1983), and reflect the various injury risks resulting from occupational, environmental or social conditions (Collier & Primeau, 2019;Delgado-Darias, Alberto-Barroso, & Velasco-Vázquez, 2018;Lambert & Welker, 2017). Nevertheless, populationwide trauma patterns in UP humans have barely been researched.…”
mentioning
confidence: 99%
“…In our recent article (Kranioti et al, 2019), we conducted an exhaustive investigation of the fracture patterns presented by the Upper Paleolithic calvaria from Cioclovina, Romania. Using forensic criteria, virtual anthropology and an experimental approach, we demonstrated that the observed fracture pattern could only have resulted from blunt force trauma (e.g., Berryman & Haun, 1996;Hart, 2005) and is evidence of perimortem trauma and interpersonal violence, concurring with the previous interpretation of Ullrich (1979).…”
mentioning
confidence: 99%